Rhizosphere Mortierella strain of alfalfa exerted weed growth inhibition by inducing expression of plant hormone-related genes - Du, Taotao; Qu, Xudong; Wang, Yibo; Li, Meixuan; Qie, Xihu; Jin, Jing; Gao, Yuxuan; Wang, Zengyu; Lin, Kejian; Yang, Chao; Sun, Juan (Frontiers in Microbiology, 2024)
Weeds are significant factors that detrimentally affect crop health and hinder optimal herbage yield. Rhizosphere microorganisms play crucial roles in plant growth, development, and nutrient uptake. Therefore, research focusing on weed control through the lens of microorganisms has emerged as a prominent area of study. The oil-producing fungus Mortierella, which is known for its numerous agricultural benefits, has garnered significant attention in recent years. In this study, we conducted inoculation experiments in a controlled artificial culture climate chamber to investigate the effects of differential hormones and differentially expressed genes in the stems and leaves of Digitaria sanguinalis using Liquid Chromatography Tandem Mass Spectrometry and RNA-seq techniques, respectively. Additionally, Pearson’s correlation analysis was used to establish correlations between differential hormones and growth indicators of Digitaria sanguinalis. The results demonstrated that inoculation with Mortierella sp. MXBP304 effectively suppressed aboveground biomass and plant height in Digitaria sanguinalis. Furthermore, there was significant upregulation and downregulation in the expression of genes involved in the synthesis and metabolism of phenylalanine and L-phenylalanine. Conversely, the expression of genes related to tryptophan, L-tryptophan, and indole was significantly downregulated. The addition of Mortierella sp. MXBP304 can influence the gene expression associated with phenylalanine and tryptophan synthesis and metabolism during Digitaria sanguinalis growth, subsequently reducing the relative contents of phenylalanine and tryptophan, thereby directly inhibiting Digitaria sanguinalis growth.